Anatomy of the Italian populist breakthrough: a 'demarcationist' fuel driving Lega and Five-star Movement electoral success?. Issue 1 (2nd January 2022) - Emanuele, Vincenzo; Santana, Andrés; Rama, José
ABSTRACT: At the 2018 general election, Italy's two main populist parties, the Five-star Movement (M5s) and the League (Lega), achieved unprecedented success. They secured an absolute majority of votes and seats and eventually gave birth to the first government in Western Europe to be composed entirely of populist parties. Although the two parties are today located on opposite sides of the political spectrum, their experience of governing together raises relevant questions about the compatibility of their electorates. Using individual-level survey data, in this article we analyse the predictors of electoral support for the two parties. Empirical results show that the parties' voters occupy opposing positions on the left-right dimension and do not share all populist traits but share a 'demarcationist' profile, as not only the Lega but also the M5s is influenced by anti-EU and anti-immigration attitudes.